Performance analysis of MIMO adaptive modulation system over fading channel model - Moungnou, Phichet; Kungmat, Tharaton (My University, 2007)
This paper analyzes the performance of the adaptive modulation system for Multiple Input Multiple Output (MIMO) over Nakagami-m fading channel, which utilizing four modulation modes. The optimization of modulation switching levels are set for maintain the target BER which is desired by many data services. Under this condition, the performance analysis of the throughput and the transmission outage probability of the adaptive modulation for MIMO system are presented. Finally, the simulation results show that the adaptive modulation for open loop and close loop MIMO system can theoretical achieve good performance with high throughput and low transmission outage probability.
Keywords: Adaptive modulation; Close loop (CL); Multiple Input Multiple Output (MIMO); Open loop (OL)